Behavioral and proteomic studies reveal methylglyoxal activate pathways associated with alzheimer’s disease - Patil, Gouri; Kulsange, Shabda; Kazi, Rubina; Chirmade, Tejas; Kale, Vaikhari; Mote, Chandrashekhar; Aswar, Manoj; Koratkar, Santosh; Agawane, Sachin; Kulkarni, Mahesh (ACS Pharmacology & Translational Science, 2022)
Diabetes is one of the major risk factors for Alzheimer’s disease (AD) development. The role of elevated levels of glucose, methylglyoxal (MGO), and advanced glycation end products (AGEs) in the pathogenesis of AD is not well understood. In this pursuit, we studied the role of methylglyoxal in the pathogenesis of AD in rat models. The elevated plus-maze (EPM) behavioral study indicated that MGO induces anxiety. Treatment of telmisartan (RAGE expression inhibitor) and aminoguanidine (MGO quencher) attenuated MGO induced anxiety. Further, hippocampal proteomics demonstrated that MGO treated rats differentially regulate proteins involved in calcium homeostasis, mitochondrial functioning, and apoptosis, which may affect neurotransmission and neuronal plasticity. The hippocampal tau phosphorylation level was increased in MGO treated rats, which was reduced in the presence of aminoguanidine and telmisartan. The plasma fructosamine level was increased upon MGO treatment. Hippocampal histochemistry showed vascular degeneration and neuronal loss upon MGO treatment. This study provides mechanistic insight into the role of MGO in the diabetes-associated development of AD.